Omega-3 fatty acid synergy with glucocorticoid in mouse lupus macrophage model: targeting pathogenic pathways to reduce steroid dependence - Heine, Lauren K.; Nault, Rance; Jackson, Jalen; Anderson, Ashley N.; Harkema, Jack R.; Olive, Andrew J.; Pestka, James J.; McDonald, Olivia F. (Frontiers in Immunology, 2025)
IntroductionSystemic lupus erythematosus (SLE) is a complex autoimmune disorder characterized by aberrant inflammation, type I IFN-stimulated gene (ISG) expression, and autoantibody production. Glucocorticoids (GCs) like dexamethasone (DEX) are standard long-term SLE treatments but cause significant side effects, highlighting the need for safer steroid-sparing options. Preclinical and clinical studies suggest that dietary supplementation with omega-3 fatty acids (O3FAs), particularly docosahexaenoic acid (DHA), suppresses inflammation and autoimmunity associated with SLE disease progression. We explored the steroid-sparing potential of DHA to influence the suppressive effects of DEX on pathogenic gene expression.MethodsMacrophages from SLE-prone NZBWF1 mice were first subjected to DHA (5, 10, or 25 µM), DEX (1, 10, 100, or 1000 nM), or DHA+DEX cotreatment. Following pretreatment, cells were exposed to lipopolysaccharide (LPS; 20 ng/mL) to model SLE hyperinflammation. Resultant gene expression was subjected to synergy and deconvolution analysis.ResultsqRT-PCR indicated that subinhibitory concentrations of DHA (5-10 µM) potentiated the efficacy of low-dose DEX (1–100 nM) in suppressing LPS-induced ISG expression (e.g., Irf7, Oasl1, Rsad2), amplifying the effects of DEX monotherapy by 10- to 100-fold. SynergyFinder analysis confirmed that DHA and DEX interacted synergistically in suppressing ISG expression, with significant inhibition observed at concentrations as low as 1 nM DEX and 5 µM DHA. RNA-seq revealed that combining suboptimal DHA (10 μM) and DEX (100 nM) induced 247 differentially expressed genes (DEGs) at 4 hr and 347 DEGs at 8 hr post-LPS, dramatically surpassing the effects of each treatment alone. Functional enrichment analysis indicated DHA+DEX cotreatment robustly suppressed immune and inflammatory pathways while promoting proliferative and metabolic processes, reflecting a shift from inflammatory (M1) to pro-resolving (M2) macrophage phenotypes. DHA and DEX countered LPS effects by i) downregulating common transcription factors (TFs) canonically associated with inflammation (e.g., NF-κB, AP-1, STATs, and IRF1), ii) upregulating shared regulatory factors involved in inflammation resolution (e.g., YBX1, EGR1, and BCL6), and iii) selectively influencing other regulatory factors.DiscussionAltogether, DHA and DEX synergistically suppress inflammatory gene expression by targeting common and unique molecular pathways in SLE macrophages, favoring the pro-resolving M2 phenotype. O3FA-GC cotreatment might facilitate reducing requisite steroid dosages for SLE management.